UPAYA PENINGKATAN PEMBELAJARAN LOMPAT JAUH DENGAN MEDIA POA PADA SISWA KELAS IV SDI AL-AZHAR YOGYAKARTA - Masnur Ali; Ria Lumintuarso (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2017)
Abstrak. Peralatan Olahraga Anak (POA) pada siswa kelas IV SD ISLAM AL-AZHAR 31 Yogyakarta 2015.Penelitian ini merupakan penelitian tindakan kelas (PTK) yang terdiri dari dua siklus. Objek penelitian adalah siswa kelas IV SD ISLAM AL-AZHAR 31 YOGYAKARTA berjumlah 32 siswa. Data dikumpulkan melalui: (1) observasi hasil belajar lompat jauh dengan media Peralatan Olahraga Anak (POA), (2) observasi proses pembelajaran, (3) observasi terhadap perilaku siswa, dan (4) tes pengetahuan. Hasil penelitian menunjukkan bahwa pembelajaran lompat jauh dengan menggunakan media Peralatan Olahraga Anak (POA) mengalami peningkatan. Kata Kunci : lompat jauh, media POA Abstract. This research aims to improve the teaching learning process of long jump through media of aids sport at students of grade fouth of SD ISLAM alzhar Yogyakarta in the academic year of 2015. This research is categorized into action research which was consisted of two cycles. The object of this research was the students of fourth grade at students of grade fouth of SD ISLAM alzhar Yogyakarta in the academic year of 2015 consist of 32 students. The data were collected through (1) the observation of students the learning result through media Peralatan Olahraga Anak (POA), (2) the observation of the teaching learning process, (3) the observation of students’ behavior, and (4) academic test. The results showed that the long jump learning by using media Sporting Goods Children (POA) increased.Keyword : long jump, POA media